Ewolucja modeli lobbingu – wpływ gospodarki opartej na informacjach i wiedzy - Molęda-Zdziech, Małgorzata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The text analyzes institutionalization of lobbying and its ties with democracy, and compares models of lobbying (pluralistic – model typical for the USA, UK, neo-corporativistic – model typical for Western Europe and Poland and the EU model). Then, lobbying is showed in the context of changes caused by the development of knowledge and information-based economy, particularly wikinomy – economy based on cooperation. The development of new technologies and the rules of global cooperation, which are the key elements of this economy, influence the creation of new lobbying strategies. This is the cause of evolution of contemporary models of lobbying in the direction of grassroots lobbying which can take different forms: from mass protests to network and internet actions. This is now called cyberlobbying and can be applied to different forms of lobbying: political, economic and social.